The Coronavirus Health Crisis, Social Media, and Online Health Information Seeking Behaviour of Older Adults in Nigeria - Bibian Ugoala; Silas Udenze (Türkiye İletişim Araştırmaları Dergisi)
Older adults or the elderly are part of the group of peeople that make up a majority of the health burdensin society, and the outbreak of coronavirus or COVID – 19 has further placed them in a risky positiondue to their age. Going by the latter statement, the research examines the impact of social media on thispopulation’s online health information-seeking behaviour in the face of the global coronavirus health crisisin Nigeria. The study employed Krejcie and Morgan’s (1970) technique for ascertaining the sample size for agiven population, and arrived at a sample of 384 quantitatively surveyed through a questionnaire. The studyconcluded that social media positively impacted the health behaviour of the research population, and theinformation sought on social media is reliable, and it also influenced their behaviour positively. However,the authors warn that online health information seekers, especially older adults, should always exercisecaution as not all information obtained on social media on various health issues, including the coronavirus,is accurate. Besides, consumers of online health information should be thorough and active users of socialmedia; they should use their human senses to discern between false and true health information. Further,they should also verify such information with health professionals if the need arises. Given the limitationsenumerated in this study, the authors suggest that further studies are essential to validate the results of thisresearch.